2023
DOI: 10.1186/s12943-023-01742-w
|View full text |Cite
|
Sign up to set email alerts
|

Transfer RNA-derived small RNAs in tumor microenvironment

Abstract: Transfer RNAs (tRNAs) are a class of non-coding RNAs responsible for amino acid translocation during protein synthesis and are ubiquitously found in organisms. With certain modifications and under specific conditions, tRNAs can be sheared and fragmented into small non-coding RNAs, also known as tRNA-derived small RNAs (tDRs). With the development of high-throughput sequencing technologies and bioinformatic strategies, more and more tDRs have been identified and their functions in organisms have been characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…In terms of clinical application prospects, tsRNAs can serve as living markers for early tumor diagnosis and disease monitoring owing to their spatiotemporal and tissue speci cities. Furthermore, they can aid in the precision treatment of tumors (9,10,33). Numerous studies have reported differential expression of tsRNAs in LC patients, with some tsRNAs showing potential for early diagnosis and prognosis of LC.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of clinical application prospects, tsRNAs can serve as living markers for early tumor diagnosis and disease monitoring owing to their spatiotemporal and tissue speci cities. Furthermore, they can aid in the precision treatment of tumors (9,10,33). Numerous studies have reported differential expression of tsRNAs in LC patients, with some tsRNAs showing potential for early diagnosis and prognosis of LC.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the research on tsRNA and disease disorders has gradually become a hot topic, mainly focusing on tumor diseases such as gastric cancer, lung cancer and hepatocellular carcinoma, neurodegenerative disorders and so on (23,24). However, there are no reports on the characteristics and changing patterns of tsRNA expression in WAT of VD de ciency young male mice with or without obesity, beside, the role and mechanism are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…These fragments are categorized into distinct types: tRF-1, tRF-3, tRF-5, tRF-2, and i-tRF, based on their specific sites of origin within these molecules [ 56 ]. Among them, tRF-1 (14–30 nt) is generated by RNase Z/ELAC2 catalyzing the cleavage of the 3’ end of pre-tRNAs and has a poly U characteristic, thus also known as 3’UtRF [ 57 ]. tRF-3 is produced by Dicer and ANG cleaving the TψC loop of mature tRNAs and can be further stratified into tRF-3a (18 nt) and tRF-3b (22 nt) based on its length [ 32 ].…”
Section: Discovery Biogenesis and Regulatory Mechanism Of Tsrnasmentioning
confidence: 99%
“…Although the potential mechanisms regulating the biogenesis of tRFs remain unclear, increasing evidence suggests that tRNA modifications, such as 5-methylcytosine (m5C), N7-methylguanosine (m7G), and pseudouridine (Ψ), play significant roles in tRNA cleavage and fragment generation [ 57 ]. On one hand, tRNA modifications can increase the stability of tRNA structure, protecting them from being cleaved by nucleases to produce tsRNAs.…”
Section: Discovery Biogenesis and Regulatory Mechanism Of Tsrnasmentioning
confidence: 99%